Placements and Sustainability Program of Business Courses in Selected Higher Educational Institutions in Metro Manila: Basis for Academic and Industry Partnership Plan (International Journal of Scientific Research and Management (IJSRM), 2023)
The present professional climate for graduates is very volatile, owing to the unpredictability of corporate restructures, technological advancements, outsourcing, and remote working, among other factors. This new professional context has prompted a philosophical rethinking of what constitutes acceptable employability learning. Due to restrictions imposed by the COVID-19 epidemic, many students doing professional placements and internships were force to leave their actual location of employment. Some students completing professional experiences lost their orders, while others accepted job arrangements that required them to work remotely online. Work readiness and preparedness played a vital role in business goal in today’s pandemic since it influences graduate success in the workforce. Many businesses want to hire new graduates because they believe they will bring new and innovative ideas to the company, but it is essential that the graduates be work-ready and prepared to do the job properly. The business provides work preparation and pre-employment training to freshly graduated employees. Furthermore, as the professional world moves toward a more flexible working arrangement that may include a remote workplace environment mixed with an office environment, this paper examines the potential benefit of their experiences in terms of being more capable in online work skills as a result of remote working.